Considerations of line and stroke: Elements of communication that transcend artistic expression - Esgueva López, María Victoria; Arros-Aravena, Alejandro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The gestural stroke and the line, originating in the field of drawing and the visual arts, have various functions, as well as numerous communicative purposes. In this work, we first carry out a study of their main functions: representative, symbolic and expressive. Subsequently, we will corroborate how this graphic element reveals a decisive contribution of information and content in manifestations and areas of knowledge outside the arts.